2006
DOI: 10.3317/jraas.2006.038
|View full text |Cite
|
Sign up to set email alerts
|

Chronic blockade of angiotensin II AT1-receptors increased cell-to-cell communication, reduced fibrosis and improved impulse propagation in the failing heart

Abstract: PaperAbstract I In nt tr ro od du uc ct ti io on n. . The influence of chronic administration of losartan on gap junction conductance (gj), conduction velocity and interstitial fibrosis was investigated in the failing heart of 4-month-old cardiomyopathic hamsters (TO-2).After two months of administration of losartan (25 mg/kg/day/po) the number of cell pairs showing very low values of gj (2-8 nS) was significantly reduced whereas the group of cell pairs with larger values of gj (18-45 nS) was significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…In addition, AT 1 receptor activation mediates a growth response in several cell types, in particular, endothelial cells and cardiomyocytes (de Gasparo, Catt, Inagami, Wright, & Unger, 2000). Moreover, AT 1 receptor blockers are effective in decreasing interstitial cardiac fibrosis in the failing heart (De Mello & Specht, 2006). A study of the effects of Ang II in adult rats showed myocyte hypertrophy and midmyocardial interstitial fibrosis (Grobe et al, 2007).…”
Section: Angiotensin IImentioning
confidence: 99%
“…In addition, AT 1 receptor activation mediates a growth response in several cell types, in particular, endothelial cells and cardiomyocytes (de Gasparo, Catt, Inagami, Wright, & Unger, 2000). Moreover, AT 1 receptor blockers are effective in decreasing interstitial cardiac fibrosis in the failing heart (De Mello & Specht, 2006). A study of the effects of Ang II in adult rats showed myocyte hypertrophy and midmyocardial interstitial fibrosis (Grobe et al, 2007).…”
Section: Angiotensin IImentioning
confidence: 99%
“…Angiotensin receptor inhibitors such as losartan appear to be effective in reducing cardiac fibrosis in a variety of models in animals and in humans. 36,37 Thus, compared to generally antagonizing TGF␤ signaling, angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists may be useful approaches to control fibrotic disease. …”
Section: Angiotensin IImentioning
confidence: 99%
“…The contribution of the RAS to HF was further supported by evidence that the density of AT 1 receptors increased in the ventricles of cardiomyopathic hamsters early during the development of the disease before apparent myocardial damage (Lambert et al 1995). In fact, it was shown that blockade of the AT 1 receptor has beneficial effects on the cardiac structure and performance in UM-X7.1 hamsters (Nakamura et al 1994) and decreased cardiac remodeling in Bio TO-2 cardiomyopathic hamsters (De Mello and Specht 2006;Shimizu et al 2006). This may again justify therapeutic targeting of the angiotensin II system in the treatment of DMD.…”
Section: Animal Models For Hf In Dmd and Bmdmentioning
confidence: 60%